ANALISIS SISTEM INFORMASI AKUNTANSI PENJUALAN PADA PT. DAIHATSU BANDA ACEH - Eva Susanti; Cut Fitrika Syawalina; Nana Ismaida (University Muhammadiyah Aceh, 2021)
This research was conducted at PT. Daihatsu Banda Aceh City. This study aims to see and analyze the sales accounting information system at PT. Daihatsu Banda Aceh City. In obtaining data, the data techniques used are field research and library research. The method used in this research is descriptive method, by collecting, classifying and interpreting data about the problems observed by the research object. so that it can provide a clear picture of the problem under study. The results showed that PT. Daihatsu Banda Aceh City carries out sales which consist of two systems, namely: a cash sales system and a credit sales system. The two systems are almost the same in implementation. Overall, the sales accounting information system, both cash and credit, which is run in the company, has been well executed by using a computerized system that fulfills the functions and objectives of the sales accounting information system. PT. Daihatsu Banda Aceh City does not store between the warehouse function and the delivery function. This results in the task of the warehouse function becoming a heavy task because of the task and will also have an impact on fraudulent actions in duties and responsibilities